Frontline staff motivation levels and health care quality in rural and urban primary health facilities: A baseline study in the Greater Accra and Western regions of Ghana - Robert Kaba Alhassan; Edward Nketiah-Amponsah (Health Economics Review, 2016)
Background: The population of Ghana is increasingly becoming urbanized with about 70 % of the estimated 26.9 million people living in urban and peri-urban areas. Nonetheless, eight out of the ten regions in Ghana remain predominantly rural where only 32.1 % of the national health sector workforce works. Doctor-patient ratio in a predominantly rural region is about 1:18,257 compared to 1:4,099 in an urban region. These rural-urban inequities significantly account for the inability of Ghana to attain the health related Millennium Development Goals (MDGs) before the end of 2015. Purpose: To ascertain whether or not rural-urban differences exist in health worker motivation levels and quality of health care in health facilities accredited by the National Health Insurance Authority in Ghana. Methods: This is a baseline quantitative study conducted in 2012 among 324 health workers in 64 accredited clinics located in 9 rural and 7 urban districts in Ghana. Ordered logistic regression was performed to determine the relationship between facility geographic location (rural/urban) and staff motivation levels, and quality health care standards. Results: Quality health care and patient safety standards were averagely low in the sampled health facilities. Even though health workers in rural facilities were more de-motivated by poor availability of resources and drugs than their counterparts in urban facilities (p < 0.05), quality of health care and patient safety standards were relatively better in rural facilities. Conclusion: For Ghana to attain the newly formulated sustainable development goals on health, there is the need for health authorities to address the existing rural-urban imbalances in health worker motivation and quality health care standards in primary healthcare facilities. Future studies should compare staff motivation levels and quality standards in accredited and non-accredited health facilities since the current study was limited to health facilities accredited by the National Health Insurance Authority.
Keywords: 330; Ghana; Rural-urban; Health worker motivation; Quality health care; Health facilities